Ageing well in the right place: partnership working with older people. Issue 1 (13th March 2017) - Sixsmith, Judith; Fang, Mei Lan; Woolrych, Ryan; Canham, Sarah L.; Battersby, Lupin; Sixsmith, Andrew
Abstract : Purpose: The provision of home and community supports can enable people to successfully age-in-place by improving physical and mental health, supporting social participation and enhancing independence, autonomy and choice. One challenge concerns the integration of place-based supports available as older people transition into affordable housing. Sustainable solutions need to be developed and implemented with the full involvement of communities, service organizations and older people themselves. Partnership building is an important component of this process. The purpose of this paper is to detail the intricacies of developing partnerships with low-income older people, local service providers and nonprofit housing associations in the context of a Canadian housing development. Design/methodology/approach: A community-based participatory approach was used to inform the data collection and partnership building process. The partnership building process progressed through a series of democratized committee meetings based on the principles of appreciative inquiry, four collaboration cafés with nonprofit housing providers and four community mapping workshops with low-income older people. Data collection also involved 25 interviews and 15 photovoice sessions with the housing tenants. The common aims of partnership and data collection were to understand the challenges and opportunities experienced by older people, service providers and nonprofit housing providers; identify the perspectives of service providers and nonprofit housing providers for the provision and delivery of senior-friendly services and resources; and determine actions that can be undertaken to better meet the needs of service providers and nonprofit housing providers in order to help them serve older people better. Findings: The partnership prioritized the generation of a shared vision together with shared values, interests and the goal of co-creating meaningful housing solutions for older people transitioning into affordable housing. Input from interviews and photovoice sessions with older people provided material to inform decision making in support of ageing well in the right place. Attention to issues of power dynamics and knowledge generation and feedback mechanisms enable all fields of expertise to be taken into account, including the experiential expertise of older residents. This resulted in functional, physical, psychological and social aspects of ageing in place to inform the new build housing complex. Research limitations/implications: The time and effort required to conduct democratized partnerships slowed the decision-making process. Originality/value: The findings confirm that the drive toward community partnerships is a necessary process in supporting older people to age well in the right place. This requires sound mechanisms to include the voice of older people themselves alongside other relevant stakeholders. Ageing well in a housing complex requires meaningful placemaking to include the functional, physical, psychological and social aspects of older people's everyday life in respect to both home and community.